Technological Convergence Of Consumer Electronics Products: A Study of Consumer Behavior and Business Strategy Toward Value Creation - Bonggas, David; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2012)
Technological convergence creates an evolution for different technological systems to evolve toward performing similar tasks. Those tasks were previously performed in separate devices, which now can be integrated into one integrated device. Separate technologies such as voice (and telephony features), data (includes basic office tasks and other productivity application) and video now share resources and interact with each other synergistically. Learning from case by case of three major converged products in the consumer electronics industry, it is a certain that in the 21st century is fast integrating the worldâ€™s media, telecommunication and information technology and online industries under a single platform.The consumers themselves are getting more educated and aware for his condition, while they are purchasing the products not only by its price, but starting to consider the key feature and value benefit which offered by the brands for them. On the consumer choice pattern it is certain that the acceptance of the concept of technological convergence might not be applied to the entire product yet by seeing case by case among product tested, it could bring some evidences that the key convergence feature has not yet absorbed by the diverged products. However, it still indicates that there will be a time when the quality of converged features are over the diverged one, which can result that a consumer will choose to use the â€œmulti-featureâ€ device instead of a single-featured device. The stages that have led to the transformation of digital convergence have left an impact with the passing of each era of the timeline. Comparing to the last decade, in this era, software and services are become a major part required to win the competition within the converged products. Keywords: technology, convergence, media, marketing, strategy, value